Alpha and beta cortical activity during guitar playing: task complexity and audiovisual stimulus analysis. (1st October 2020) - Leite, José Artur Aragão; dos Santos, Mateus Antônio Cândido; da Silva, Rafael Mariano Camilo; Andrade, Adriano de Oliveira; da Silva, Gustavo Moreira; Bazan, Rodrigo; de Souza, Luciane Aparecida Pascucci Sande; Luvizutto, Gustavo José
Abstract: Purpose: Some studies have explored the relationship between music and cortical activities; however, there are just few studies investigating guitar performance associated with different sensory stimuli. Our aim was to evaluate alpha and beta activity during guitar playing. Materials and Method: Twenty healthy right-handed people participated in this study. Cortical activity was measured by electroencephalogram (EEG) during rest and 4 tasks (1: easy music with an auditory stimulus; 2: easy music with an audiovisual stimulus; 3: complex music with an auditory stimulus; 4: complex music with an audiovisual stimulus). The peak frequency (PF), median frequency (MF) and root mean square (RMS) of alpha and beta EEG signals were assessed. Results: A higher alpha PF at the T3-P3 was observed, and this difference was higher between rest and task 3, rest and task 4, tasks 1 and 3, and tasks 1 and 4. For beta waves, a higher PF was observed at C4-P4 and a higher RMS at C3-C4 and O1-O2. At C4-P4, differences between rest and tasks 2 and 4 were observed. The RMS of beta waves at C3-C4 presented differences between rest and task 3 and at O1-O2 between rest and task 2 and 4. Conclusion: The action observation of audiovisual stimuli while playing guitar can increase beta wave activity in the somatosensory and motor cortexes; and increase in the alpha activity in the somatosensory and auditory cortexes and increase in the beta activity in the bilateral visual cortexes during complex music execution, regardless of the stimulus type received. Abbreviations: bpm: beats per minute; C: central; EEG: electroencephalogram; F: frontal; Hz: hertz; LABCOM: Laboratory of Motor Control and Biomechanics; MD: mean difference; MF: median frequency; O: occipital; P: parietal; PF: peak frequency; R: rest; RMS: root mean square; T: temporal; T1: task 1; T2: task 2; T3: task 3; T4: task 4; UFTM: Federal University of Triângulo Mineiro